The Role of Cooperative Learning in Undergraduate Engineering Education: A Better Alternative to Teacher-Centered Learning - Firdhaus, Ahmad; Hakim, Muhammad Luqman; Tuswan, Tuswan; Mursid, Ocid (CV. Ulil Albab Corp, 2025)
This comprehensive analysis examines the effectiveness of cooperative learning (CL) in undergraduate engineering education, contrasting it with traditional teacher-centered methods. The study finds that CL enhances academic performance and develops essential skills such as critical thinking, teamwork, and communication. Unlike passive teacher-centered methods, CL promotes active participation and collaborative problem-solving, better aligning educational outcomes with the demands of the engineering profession. The article highlights the limitations of teacher-centered learning, which often fails to foster deep understanding or student engagement. CL, involving students in diverse, role-defined groups, helps them connect theory to practice, particularly benefiting first-year students transitioning into collaborative environments. However, challenges to implementing CL include student resistance, higher instructor workload, and the need for effective group management. The study stresses the importance of faculty training, discipline-specific resources, and structured support to address these obstacles. Ultimately, the article advocates for a shift toward CL in engineering education, emphasizing its potential to prepare students for collaborative, dynamic engineering roles in a technologically advanced world.